Architecture of 2D MoS2 nanosheets and 3D CdMoS4 marigold flowers: consequence of annealing on field emission performance - Kadam, Sunil R.; Suryawanshi, Sachin R.; Panmand, Rajendra P.; Mate, Vivek R.; More, Mahendra A.; Late, Dattatray J.; Kale, Bharat B. (Microporous and Mesoporous Materials, 2016)
Herein, we report the field electron emission investigations on template free solvothermally synthesized layered MoS2 nanosheets as well as novel phase of CdMoS4 nanoflowers at the base pressure of similar to 1 x 10(-8) mbar. The turn-on field, threshold field and maximum emission current densities for both MoS2 and CdMoS4 are strongly influenced by thermal annealing in inert atmosphere. The turn on field, required to draw emission current density of 1 mu A/cm(2) is found to be 5.8 and 3.2 V/mu m for pristine and annealed MoS2 at 400 degrees C. In case of as prepared and annealed CdMoS4 sample the turn on field values are found to be similar to 6.2 and 5.0 V/mu m, respectively. The emission current versus time (I-t) plot measured at the preset current values of similar to 1 mu A for pristine and annealed sample indicates stable operation of the emitter. The emission current fluctuations for annealed sample are observed to be less as compared with the pristine sample due to conditioning of the emitter, thereby showing highly stable nature of emitter. Thus, the present result demonstrates the potential of annealed MoS2 nanosheets and CdMoS4 nanoflowers as an emerging materials for micro/nanoelectronics and flat panel field emission display applications. (C) 2016 Elsevier Inc. All rights reserved.
Keywords: field emission; MoS2 and CdMoS4; Nanoflowers; nanosheets